miR-155 Accelerates the Growth of Human Liver Cancer Cells by Activating CDK2 via Targeting H3F3A - Xin, Xiaoru (Mol Ther Oncolytics, 2020)
miR-155 is associated with the promotion of tumorigenesis. Herein, we indicate that abnormal miR-155 was negatively correlated with the expression of P21WAF1/Cip1. Our results suggest that miR-155 alters the transcriptome and inhibits the expression of H3F3A in liver cancer cells. Therefore, miR-155 inhibits the methylation modification of histone H3 on the 27(th) lysine. Notably, on the one hand, miR-155-dependent CTCF loops cause the CDK2 interacting with cyclin E in liver cancer cells; on the other hand, miR-155 promotes the phosphorylation modification of CDK2 by inhibiting H3F3A. Subsequently, miR-155 competitively blocks the binding of RNA polymerase II (RNA Pol II) to the P21WAF1/CIP1 promoter by increasing the phosphorylation of CDK2, inhibiting the transcription and translation of P21WAF1/CIP1. Strikingly, excessive P21WAF1/CIP1 abolishes the cancerous function of miR-155. In conclusion, miR-155 can play a positive role in the development of liver cancer and influence a series of gene expression through epigenetic regulation.